Multimodality liver directed treatment for colorectal liver metastasis: Array of complementary options can improve outcomes - A single centre experience from India - Patkar, Shraddha; Chopde, Amit; Shetty, Nitin; Kulkarni, Suyash; Gala, Kunal Bharat; Chandra, Daksh; Ramaswamy, Anant; Ostwal, Vikas; Goel, Mahesh (Frontiers in Oncology, 2023)
AIM Complimentary use of Liver directed therapies (LDTs) with systemic chemotherapy has improved oncologic outcomes in colorectal liver metastasis (CRLM). We analysed institutional results of multimodality management. Methods Retrospective analysis of prospectively maintained database of CRLM patients managed with LDT including surgical resection, Ablation, Transarterial chemoembolization (TACE) or Transarterial radioembolization (TARE) between November 2011 to March 2020. Management plan was decided in multidisciplinary meeting. Resectable tumours underwent surgical resection or ablation or both in some cases. Borderline resectable or unresectable disease was treated with down staging chemotherapy or TACE/TARE followed by resection or ablation. All patients received adjuvant chemotherapy. Factors influencing survival were analysed. Results Out of total 375 patients, surgery alone was done in 191 (50.93%) patients while surgery with other LDT in 26 patients (6.93%). Ablation alone was done in 100 (26.66%) whereas TACE/TARE were done as standalone treatment in 21 (5.6%) and 7 (1.86%) patients respectively. TACE + ablation was done in 28 (7.46%) and TARE + ablation was done in 2(0.53%) patients.5-year Overall Survival(OS) was 49.8% while Event free survival(EFS) was 21.4%. The median OS and EFS for surgical group was significantly better than non-surgical group (78 V/s 39 months; p<0.05 and 20 V/s 15 months p <0.005). The resectable (78 months) group had better median OS as compared to borderline resectable and Unresectable group (39 months and 29 months). Male gender, resectable disease and surgical intervention were associated with improved OS. Conclusion Although surgery remains the mainstay of treatment, complementary use of non-surgical LDT with systemic therapy offers possibility of good outcomes in advanced liver limited disease. Our experience highlights the impact of multidisciplinary care in optimizing CRLM treatment.